2023
DOI: 10.1186/s40798-023-00585-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Muscle Quality in Older Individuals: A Systematic Scoping Review with Meta-Analyses

Abstract: Background The quantity and quality of skeletal muscle are important determinants of daily function and metabolic health. Various forms of physical exercise can improve muscle function, but this effect can be inconsistent and has not been systematically examined across the health-neurological disease continuum. The purpose of this systematic scoping review with meta-analyses was to determine the effects and potential moderators of exercise training on morphological and neuromuscular muscle qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…Aerobic exercise, strength training, explosive-force training, flexibility training, balance training, and multi-component intervention can all improve the degree of sarcopenia in older patients [72]. A study involving 1,494 older patients showed that the intervention of resistance training, aerobic exercise, and balance training can improve the walking speed, muscle strength, exercise ability, and physical function of weak patients [73]. Strength training can improve skeletal muscle strength and is an important way to prevent skeletal muscle attenuation and falls; it is also a key factor in maintaining the functional ability of older people.…”
Section: Prevention and Treatment Of Cognitive Frailty In Patients Wi...mentioning
confidence: 99%
“…Aerobic exercise, strength training, explosive-force training, flexibility training, balance training, and multi-component intervention can all improve the degree of sarcopenia in older patients [72]. A study involving 1,494 older patients showed that the intervention of resistance training, aerobic exercise, and balance training can improve the walking speed, muscle strength, exercise ability, and physical function of weak patients [73]. Strength training can improve skeletal muscle strength and is an important way to prevent skeletal muscle attenuation and falls; it is also a key factor in maintaining the functional ability of older people.…”
Section: Prevention and Treatment Of Cognitive Frailty In Patients Wi...mentioning
confidence: 99%
“…Muscle quality, a term used to characterize muscle's capacity for contraction, metabolic activity and electrical activity, plays a crucial role in various populations, particularly in low functioning older adults and those with muscle diseases like sarcopenia (Naimo et al, 2021). The concept of muscle quality encompasses both micro-and macroscopic aspects of muscle architecture and composition and has gained increasing attention with inclusion in the definition of sarcopenia, indicating the significance of muscle quality in evaluating muscle function and strength among older individuals (Cruz-Jentoft et al, 2019;Hortobágyi et al, 2023;Radaelli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, muscle quality is not solely determined by the size and composition of the muscles, but also by the efficiency and effectiveness of the neuromuscular system. Therefore, it is comprised of two major components which describe different components (Hortobágyi et al, 2023): (i) characteristics of morphological component of the non-contractile tissue; and (ii) neuromuscular component defined as the ratio between force or torque and a measure of muscle size (thickness, volume, cross-sectional area or echo intensity) (Fragala et al, 2015;Lynch et al, 1999). So far, muscle quality has been most defined as a ratio between a measure of muscle strength and muscle mass, and in the earlier research it was suggested that muscle quality is an indicator of muscle function rather than muscle strength (Lynch et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, qualitative MRI can easily identify oedema and fatty infiltration (i.e., the main pathologic features), distinguishing between active muscle inflammation and chronic muscle damage, and depicting specific patterns of muscular involvement extensively described in association with various genetic forms [ 7 ]. On the other hand, quantitative MRI is mostly used for research purposes to obtain an unbiased measurable evaluation of fatty infiltration (through fat fraction estimation with 2- or 3-point Dixon sequence), oedema (with T2 relaxometry) and early structural damage (via diffusion tensor imaging), and is also potentially useful for evaluating treatment response [ 8 , 9 , 10 ] As demonstrated in other clinical scenarios, imaging data also contain quantitative information not visible to the naked eye, known as radiomics features, which could be useful for further profiling of these patients [ 11 , 12 , 13 , 14 ]. However, extracting quantitative features from specific areas of the image requires manual segmentation, which is extremely time consuming and often subject to variability.…”
Section: Introductionmentioning
confidence: 99%